The Impact of The Funeasylearn Application on Vocabulary Mastery: A Study of Mobile Technology Use in The Context of English Language Learning as a Learning Media - Nur Insani Sakinah; A. Muliati M; Chaerul Fadlan Saud (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This research examined the effectiveness of the FunEasyLearn application in enhancing students’ English vocabulary. Using a quantitative one-group pretest–posttest design with 29 eighth-grade students at SMP Negeri 26 Makassar, data were collected through vocabulary tests. The results revealed a significant improvement in students’ vocabulary scores, increasing from an average of 55.17 in the pretest to 81.03 in the posttest, with a paired-sample test result of p = 0.000 and an N-Gain score of 0.58, indicating a medium approaching high level of improvement. These findings suggest that FunEasyLearn is an effective and engaging digital tool that can be integrated into English teaching to support both classroom instruction and independent learning.Keywords: FunEasyLearn, vocabulary learning, digital learning media, English teaching, students’ evaluation.